Genomics, physiology and behaviour of social insects - Zayed, Amro; Kent, Clement F.; Abbot, Patrick (Advances in insect physiology ;, 2015)
Physiology, Behavior, Genomics of Social Insects provides comprehensive information on the social insect groups described, including new and unique reviews on emerging model social organisms. The book's interdisciplinary approach integrates behavior, genomics, and physiology, providing readers with great insights into the present state of a rapidly expanding area of research. It also discusses areas where new research tools will bring hope to longstanding problems.